In memoriam: Carl J. Carrano - Frithjof C. Küpper; Eleanor Carrano; Kenneth N. Raymond; Eric Miller; Ricardo Cruz-López; Ana Mijovilovich; Kyoko Yarimizu; Andrew Cooksy; Wes Harris; Shady A. Amin; Alison Butler; John C. Carrano (BioMetals, 2026)
This article is a celebration of the life and work of Carl J. Carrano who, from a childhood in Long Island, New York, built a career in bioinorganic chemistry, especially in the context of metal uptake and halogen metabolism in microbes and marine organisms.